Peran Penting Psikologi dalam Pendidikan Islam - Hadi, Imam Anas (Nadwa: Jurnal Pendidikan Islam, 2017)
This study aims to determine the important role of psychology for Islamic education. The method used library research. Data collection uses documentation and data analysis with descriptive analysis. The results showed that psychology plays an important role in Islamic education as a religious consciousness associated with the values of the soul that is personality. In Islamic Psychology it is better known as term al-Syakhsiyah. The role of psychology in Islamic education is to bridge the delivery process of science to pay more attention to the psychology of each learner, this will  determine success of the transfer  process of values to students, becouse student and teacher have opened  psychology and ready to make good communication. .   AbstrakPenelitian ini bertujuan untuk mengetahui peran penting psikologi bagi pendidikan Islam. Metode yang digunakan library research. Pengumpulan data menggunakan dokumentasi dan analisa data dengan analisis deskriptif. Hasil penelitian menunjukkan bahwa psikologi berperan penting dalam pendidikan Islam yaitu sebagai penanaman kesadaran keagamaan yang berhubungan dengan nilai-nilai bathiniyah yang bersifat pribadi (personality). Dalam istilah psikolgi Islam lebih dikenal dengan term al-Syakhsiyah. Peran psikologi dalam pendidikan Islam adalah menjembatani proses penyampaian ilmu pengetahuan agar lebih memperhatikan psikologi masing-masing peserta didik,  hal ini akan sangat menentukan keberhasilan  proses transfer of values siswa.